Administrative Leaders’ Strategies as Correlates of Workers' Job Performance - Udoka Eze, Val Hyginus; Esther Eze, Chidinma; Mbabazi, Asiati; Nnenna, Ugwu Jovita (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
The study investigated the Principals’ Administrative Strategies as Correlates of Teachers’ Job Performance In Secondary Schools in Nsukka Education Zone Of Enugu State. Four research questions and four null hypotheses guided the study. A correlational survey design was adopted for this study. The population comprised 1830 principals and teaching staff. A sample size of 605 respondents was drawn using a proportionate random sampling technique. The two designed instruments used for data collection are Principals' Administrative Strategies Questionnaires (PASQ) and Teachers' Job Performance Questionnaires (TJPQ). The instrument was subjected to face validation by three experts and internal consistency of the instrument was obtained using Cronbach Alpha that yielded an index of 0.73. Data collected were analyzed using regression analysis while regression ANOVA was used in testing the formulated hypotheses at a 0.05 level of significance. The findings revealed among others that, open communication, carrying teachers along and providing for teachers’ welfare among others are principals’ administrative strategies for enhancing teachers’ job performance in public secondary schools. The result also revealed that a highly positive significant relationship exists between principals’ administrative strategies in decision-making, delegation of duties, open communication and management of staff welfare and teachers’ job performance in public secondary schools in Enugu state. The study recommended among others that principals in public secondary schools should adopt positive administrative strategies as identified in this study to promote teachers’ job performance.